2018
DOI: 10.1016/j.rser.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Modelling volatility spillovers for bio-ethanol, sugarcane and corn spot and futures prices

Abstract: The recent and rapidly growing interest in biofuel as a green energy source has raised concerns about its impact on the prices, returns and volatility of related agricultural commodities. Analyzing the spillover effects on agricultural commodities and biofuel helps commodity suppliers hedge their portfolios, and manage the risk and co-risk of their biofuel and agricultural commodities. There have been many papers concerned with analyzing crude oil and agricultural commodities separately. The purpose of this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…The analysis of univariate and multivariate conditional volatility models below is a summary of what has been presented in the literature (see, for example [18] Caporin and McAleer (2012) [19] Chang et al (2015), and especially [20] Chang et al (2017)), although a comprehensive discussion of the Full and Diagonal BEKK models is not available in any published source. In particular, the application of the quasi likelihood ratio (QLR) test of the Diagonal BEKK model as the null hypothesis against the alternative hypothesis of a Full BEKK model does not seem to have been considered in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of univariate and multivariate conditional volatility models below is a summary of what has been presented in the literature (see, for example [18] Caporin and McAleer (2012) [19] Chang et al (2015), and especially [20] Chang et al (2017)), although a comprehensive discussion of the Full and Diagonal BEKK models is not available in any published source. In particular, the application of the quasi likelihood ratio (QLR) test of the Diagonal BEKK model as the null hypothesis against the alternative hypothesis of a Full BEKK model does not seem to have been considered in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…McAleer et al (2008) showed that the QMLE of the parameters of the DBEKK model were consistent and asymptotically normal, so that standard statistical inference on testing hypotheses is valid (or further details, see Chang et al, 2018). It should be emphasized that the QMLE of the parameters in the conditional means, namely equations (1) and (5), and the conditional variances, namely equations (4) and (7), will differ as the multivariate models, (5) and (7), respectively, are estimated jointly, whereas the univariate models, (1) and (4), respectively, are estimated individually.…”
Section: Vectorization Of a Full Matrixmentioning
confidence: 99%
“…In what follows are the regression equations for three univariate conditional volatility models that are used to estimate the expected rate of change in the number of Chinese tourists. For a more detailed derivation, the interested reader may refer to McAleer (2014), and Chang, McAleer and Wang (2018).…”
Section: Olsmentioning
confidence: 99%